Study of integrated headphone MP3 / Mohd Amirul Mukmin Abd Wahab - Abd Wahab, Mohd Amirul Mukmin (Faculty of Information Technology and Quantitative Sciences, 2006)
As known as MP3 and it is a standard for audio compression that makes any music file smaller with little or no loss of sound quality. MP3 is part of MPEG, an acronym for Motion Pictures Expert Group, a family of standards for displaying video and audio using loss compression. Compression scheme used to transfer audio files via the Internet and store in portable players and digital audio servers. The MP3 player is the well-used device nowadays and apart of the users are the athletes. There are several large companies such like Sony Corporation, Philips, Panasonic, Aiwa and Apple produced their own design and brand new MP3 players.